Suspension Dynamics and Pavement Wear - de Pont, J.; Steven, B. (Engineering Transactions, 2000)
Recently a series of three accelerated dynamic loading tests was carried out at the Canterbury Accelerated Pavement Testing Indoor Facility (CAPTIF). The aim of these tests was to determine the influence of dynamic loading on pavement wear. This paper presents an investigation into the relationships between the permanent vertical surface deformation (VSD) of the pavement, the applied dynamic wheel loads and the pavement structural stiffness. It is shown that the VSD was correlated with both the pavement stiffness and the dynamic wheel forces but that the relationship with wheel forces was highly dependent on the level of dynamic loading. A surrogate measure for pavement strain formed by combining pavement stiffness and wheel force into a single parameter provided the strongest correlation with VSD. Using this "strain" parameter as the independent variable of a power law predictor for VSD gives a best fit estimate for the exponent between one and two.